The effects of macromolecular and serum supplements and oxygen tension during bovine in vitro procedures on kinetics of oocyte maturation and embryo development - Mingoti, Gisele Zoccal [UNESP]; Dias Caiado Castro, Viviane Sggobi [UNESP]; Meo, Simone Cristina; Sa Barretto, Letcia Siqueira [UNESP]; Garcia, Joaquim Mansano [UNESP] (Springer, 2011)
Aiming to standardize in vitro production of bovine embryos and to obtain supplements to replace serum in culture media, this study evaluated the nuclear maturation kinetics and embryonic development in bovine after in vitro maturation (IVM) and culture (IVC) with several macromolecules (animal origin: bovine serum albumin (BSA), fetal calf serum (FCS); synthetic: polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), Ficoll, and Knockout) at two oxygen tensions (20% and 5% O(2)). Regarding nuclear kinetics, neither the presence of the expected stage (metaphase I, transition anaphase to telophase, and metaphase II) at each evaluation moment (6, 18, and 24 h after IVM, respectively) nor the accelerated polar body emission (at 18 h after IVM) related developmental competence to blastocyst stage when different supplements were compared. Independently of supplement, cleavage rates at 20% O(2) (61.6-79.2%) were higher than at 5% O(2) (38.9-58.7%). At 20% O(2), higher blastocyst and hatching rates, respectively, were obtained in treatments BSA, FCS, Knockout, and control group (IVM with FCS and IVC with BSA + FCS, 14.0-23.5% and 6.8-15.4%) in comparison to PVA, PVP, and Ficoll (0%). The same was observed at 5% O(2) for blastocyst rates with BSA, FCS, Knockout, and control (5.4-16.8%) and for hatching rates with BSA, FCS, and control (2.0-11.1%). We can conclude that producing bovine embryos at 20% O(2) during the entire IVP process resulted in higher developmental rates than at 5% O(2). In addition, while defined macromolecules PVA, PVP, and Ficoll were not suitable for embryonic development, the synthetic serum Knockout was able to replace serum and albumin for IVP in bovine at 20% O(2).
Keywords: Cattle; Embryo; In vitro maturation; Macromolecule; Oxygen